When a health system turns into a Tower of Babel: Mozambique's experience - Namburete, Denise (Institute of Development Studies, 2018)
Likened to the Tower of Babel legend, the Mozambican national health system speaks several languages and pursues a range of different interests, answering to a number of partners and other bilateral and multilateral actors who all have some kind of circumstantial and contextual interest. When the Paris Declaration on Aid Effectiveness was endorsed, Mozambique may […]
Keywords: G - Mozambique / Moçambique; L - english / inglês; health / saúde

Mozambique’s insurgency: a new Boko Haram or youth demanding an end to marginalisation? - Hanlon, Joseph (Africa at LSE, 2018)
Joseph Hanlon argues that Mozambique’s new “Islamic” insurgency is about marginalised youth demanding to be heard, and therefore is similar to anti-establishment protest across the world.
Keywords: *snowball; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; social inclusion & exclusion / inclusão e exclusão social; youth / juventude

New Action Plan for Health Promotion in Cabo Delgado (Mozambique) (2018)
In Cabo Delgado - Mozambique, we are giving support to the Provincial Health Directorate (DPS-CD) in developing an essential tool for the promotion of health in the Province: The Action Plan for Health Promotion.
Keywords: *tagged; G - Mozambique / Moçambique; Health PEA; L - english / inglês; health / saúde

Falta de alimentos agrava-se em zonas atacadas na província de Cabo Delgado - Macuácua, Amandio Roberto (Jornal Notícias, 2018)
A falta de alimentos está a agravar-se em zonas do interior na província de Cabo Delgado por causa dos ataques causados por grupos armados que têm levado a população a abandonar terras, alerta um relatório ontem divulgado.
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict / conflito